Weather, Climate and Production Risk - Hongliang Zhang; John M. Antle (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
We investigate climate change impacts on productivity and production risk on U. S. Pacific Northwest winter wheat farms. Using farm-level data from the Census of Agriculture, we use a partial-moment-based approach to estimate climate and irrigation influences on winter wheat yield and farm net return distributions. Mean precipitation, growing degree-days, and freezing degree-days are shown to have highly distinct seasonal effects on the first three moments of the farm-level yield and net return distributions. Irrigation substantially increases the certainty equivalent of irrigated farms by shifting the winter wheat yield distribution outwards, and by increasing mean net returns but also decreasing the skewness of the net return distribution and thus reducing downside risk. By the mid-21st century, climate-change projections from 20 global climate models downscaled to the study region reveal a range of possible positive and negative effects on the winter wheat yield and net return distributions.
Keywords: C5; D8; Q1; 330; Climate Change; Winter Wheat; Production Risk; Partial Moments